Fishers perspectives on the barriers for the English inshore fleet to diversify into aquaculture. (September 2021) - Conejo-Watt, Heather; Muench, Angela; Mangi, Stephen C.; Jeffery, Keith; Hyder, Kieran
Abstract: Long-term trends in seafood production and demand indicate a need to move away from capture fisheries in favour of increased aquaculture production. The paper explores the potential social and economic barriers towards creating a more holistic seafood production chain. Fisheries not only provide food but also play a significant role in the provision of cultural ecosystem services. Diversification to a similar maritime activity is therefore a potential solution to help preserve this culturally significant activity as well as sustaining food provision and income. However, there are potential social and economic barriers that need to be understood to allow this integration of sectors to happen. This study uses the Q-methodology to investigate the integration or diversification into aquaculture in the English inshore fleet. The results indicate distinctive viewpoints of fishers on aquaculture and the barriers to integration. There were two emergent viewpoints that were positive to diversification into aquaculture and two viewpoints that were against integration. The findings suggest that there is room for policy makers to encourage diversification using measures such as providing guidance documents or training in winter downtime to help fishers to get technical knowledge on aquaculture. Moreover, aquaculture out-reach programmes, addressing public perceptions and aquaculture design consultations, run by NGO's or funded by government, may also provide an outlet for this group to learn more and help address the wants and interests of this group. To ease uncertainty for fishers, pilot projects demonstrating the potential co-location of aquaculture and fisheries, may another way to overcome the reluctance of some fishers to diversify into aquaculture. Highlights: No consensus on the barriers for the English inshore fleet to integrate with aquaculture. Identified four viewpoints with two in favour and two more reluctant for integrating fisheries with aquaculture. Lack of finance and skills/knowledge is seen as a barrier within the more pro-aquaculture fishery discourse. Occupational pride and family tradition is seen as a barrier within the anti-aquaculture fishers' perspective.